Efficacy and safety of hematopoietic stem cell transplantation vs. immunosuppressive therapy in patients with hepatitis-associated aplastic anemia: a systematic review and meta-analysis - Yaonan Hong; Qi Liu; Zhuonan Sun; Peicheng Wang; Xu Wang; Ziying Su; Yuzhu Li; Wenbin Liu; Huijin Hu; Yingying Shen; Baodong Ye; Yuhong Zhou; et al. (Hematology)
The present study aimed to compare the efficacy and safety of hematopoietic stem cell transplantation (HSCT) and immunosuppressive therapy (IST) for hepatitis-associated aplastic anemia (HAAA). Studies comparing HSCT with IST in HAAA were retrieved from inception to July 22, 2024, including 12 studies with a total of 544 cases for meta-analysis. Meta-analysis demonstrated significantly superior outcomes in the HSCT group versus IST, which was manifested as lower overall mortality (P < 0.01), higher overall response rate (P < 0.001), and improved five-year overall survival (P < 0.05), yielding a pooled RR of 1.67 (95% CI: 1.15–2.44), 0.75 (95% CI: 0.66–0.86) and 0.88 (95% CI: 0.78–0.99), respectively. However, no benefit was observed in one-year survival (P = 0.08). Further subgroup analysis indicated that the advantage of mortality (P < 0.05, RR = 1.67, 95% CI: 1.10–2.55) and five-year overall survival (P = 0.05, RR = 0.84, 95% CI: 0.71–1.00) only achieved in patients under 20 years old. There was no significant difference in the overall response and one-year overall survival for each age group. Additionally, for the IST selection, a combination of cyclosporine (CSA) and antithymocyte globulin/antilymphocyte globulin (ATG/ALG) was preferred over the CSA-only regimen (effectiveness of 78.57% vs. 50.00%), although the difference was not statistically significant (P = 0.10, RR = 1.56, 95% CI: 0.92–2.66). This study showed that HSCT had a higher effective rate, greater long-term survival and lower mortality compared to IST, especially for patients under 20 years old, who should receive HSCT treatment as possible.